Knowledge and perception regarding surgical antibiotic prophylaxis among physicians in the department of obstetrics and gynecology - Abubakar, Usman; Syed Sulaiman, Syed Azhar; Adesiyun, Adebiyi G. (Wolters Kluwer India Private Limited, 2020)
Background: Evidence shows that compliance with surgical antibiotic prophylaxis (SAP) among obstetricians and gynecologists is poor. This study evaluates the knowledge and perceptions regarding SAP among doctors in Obstetrics and Gynecology units.